Предмет: Алгебра,
автор: RomanRois
Нужно упростить выражение
Cos^2(a)-sin^2(a)
-------------------------- - tg(-a)
Cos^2(a)-sin(-a) *cos(-a)
Ответы
Автор ответа:
0
1) cos²(a)-sin²(a) = (cos(a)-sin(a))(cos(a)+sin(a))
2) cos²(a)-sin(-a)*cos(-a) = cos²(a)+sin(a)*cos(a) = cos(a)*(cos(a)+sin(a))
sin нечет
cos чет
3) (cos(a)-sin(a))(cos(a)+sin(a)):[ cos(a)*(cos(a)+sin(a))] = (cos(a)-sin(a)):cos(a) = 1-tg(a)
4) 1-tg(a)-tg(-a) = 1-tg(a)+tg(a) = 1
2) cos²(a)-sin(-a)*cos(-a) = cos²(a)+sin(a)*cos(a) = cos(a)*(cos(a)+sin(a))
sin нечет
cos чет
3) (cos(a)-sin(a))(cos(a)+sin(a)):[ cos(a)*(cos(a)+sin(a))] = (cos(a)-sin(a)):cos(a) = 1-tg(a)
4) 1-tg(a)-tg(-a) = 1-tg(a)+tg(a) = 1
Похожие вопросы
Предмет: Қазақ тiлi,
автор: aigul011992q
Предмет: Биология,
автор: velvetforaesthetic
Предмет: История,
автор: bilousdaria33
Предмет: Информатика,
автор: максим117е